Pengaruh Praktik Pemberian ASI Terhadap Risiko Stunting di Indonesia: Studi Literatur - Karima, Ulya Qoulan; Herbawani, Chahya Kharin; Puspita, Ikha Deviyanti (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Background: Stunting that occurs at the age of under two years will predict poor cognitive function in thefuture, so as this period is very important to maintain the child’s growth and development. One of which is theoptimal nutritional intake from breastfeed and complementary breastfeeding. Objective: To determine theeffect of breastfeeding practices on stunting in Indonesia based on literature searches. Methods: Literaturestudy of scientific articles in published journals in Indonesia with a population of children aged 6-23 months.Literature search was carried out through three data portals: Google Scholar, Garuda Portal, andResearchGate by using keywords: “stunting”, “ASI”, “6-23 months” and combine the keyword withcombination of (“”) and (AND). Results: 13 journals were appropriate to research topics. There are 10variables related to breastfeeding practices: early initiation of breastfeeding, colostrum, pralacteal feeding,exclusive breastfeeding, time of first complementary breastfeeding, diversity of complementary foods,frequency of complementary foods, status, duration, and length of breastfeeding. Conclusion: Most studiesfound a significant relationship between exclusive breastfeeding and stunting. However, the size of theassociation regarding how much the protective effect of exclusive breastfeeding still shows different numbers.Most of the studies found a significant association between the first time of complementary feeding andstunting.